A visit to a classroom of English language learners - Steinhorn, Pauline; Creed, Bill; Association for Supervision and Curriculum Development (Alexandria, VA : ASCD, 2004)
A look at Maria Pantin-Fernandez's second-grade classroom at Coral Way Elementary School in Miami, Fla. The school is recognized internationally as a model for bilingual education. This video helps adjusts teaching to the language level of the learners, uses gestures, pictures, lab experiments and other strategies to teach language, encourage students to peak with their peer, motivate students to learn by doing and uses teaching strategies and grouping techniques
Title from container
Executive producer, John Checkley ; editor, Bill Creed ; director of photography, Stanley Staniski ; sound, Alvaro Ganzalez
Keywords: Coral Way Elementary School (Miami, Fla.); Education, Bilingual -- Florida -- Miami; Linguistic minorities -- Education; English language -- Study and teaching